A history of German Jewish Bible translation - Gillman, Abigail 1964- (Chicago The University of Chicago Press, 2018)
Intro -- Contents -- Preface -- List of Abbreviations -- Introduction: The German Jewish Bible in Context -- 1. The First Wave: Jewish Enlightenment Bibles in Yiddish and German -- 2. The Second Wave: Emergence of a Bible Industry -- 3. The Third Wave: The Bible as Gesamtkunstwerk -- 4. The Fourth Wave: Reimagining the German Jewish Bible -- Epilogue: Ma shemo? The Name of God in the German Jewish Bible -- Acknowledgments -- Notes -- Bibliography -- Index
Includes bibliographical references and index. Description based on print version record
Keywords: Bible.-Old Testament-Translating-Germany-History; Bible ; Old Testament ; Translating ; Germany ; History; Bible ; Old Testament ; Versions, Jewish; Bible ; Old Testament ; German ; Versions; Bible ; Old Testament ; Yiddish ; Versions; Bible ; Old Testament ; Criticism, interpretation, etc., Jewish ; Germany; Judaism ; Germany ; History ; Modern period, 1750-; Electronic books